Pengaruh Kualitas Layanan Dan Kepercayaan Terhadap Loyalitas Nasabah Pada BMT NU Cabang Mayang Jember - Mila Rosa; Hersa Farida Qoriyani (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research examines the impact of service quality and trust on customer loyalty at BMT NU Cabang Mayang Jember. The study aims to identify significant relationships between these variables. A quantitative approach was used, employing questionnaires distributed to 100 respondents selected through purposive sampling. The findings indicate that service quality has a significant positive effect on customer loyalty, while trust does not significantly influence loyalty on its own. The combined effect of both variables shows a substantial impact on customer loyalty. This study contributes to understanding how service quality and trust can enhance customer loyalty in microfinance institutions.